Evaluasi Kinerja Saluran Sekunder Morokai Daerah Irigasi Samal Kanan Kabupaten Maluku Tengah - Prety Oktaviana; Rudi Serang; Maslan Abdin; Apri Adam Matitaputty (JURNAL SIMETRIK, 2026)
The Samal Kanan Irrigation Area in Central Maluku Regency, which has been operating since 2003, has experienced a decline in physical condition, particularly in the Morokai Secondary Canal. This study aims to evaluate the performance and physical infrastructure condition of the canal to determine the functional level of the irrigation system. The research employed a quantitative approach, with data collected through field surveys and discharge measurements and subsequently analyzed based on the guidelines stipulated in the Minister of Public Works and Public Housing Regulation Number 12/PRT/M/2015. The results indicate significant physical damage, including cracks, wall fractures, sedimentation, and vegetation that obstruct water flow. The measured discharge of 0.145 m³/s is lower than the design discharge of 0.594 m³/s. The Irrigation System Performance Index (ISPI) value of 58.2% falls into the poor category, indicating the need for major rehabilitation with an estimated cost of IDR 656,349,000 for a canal length of 525.36 meters. Keywords: canal discharge measurement, irrigation system performance index, Morokai Secondary Canal.